The uneven spread of Global G.A.P. certification - Insa Flachsbarth; Nina Grassnick; Bernhard Brümmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
GlobalG.A.P. compliance has often become a key requirement for farmers to access high-value global markets. Yet, the global spread of certification is highly uneven among countries. We assess the drivers and dynamics behind these unequal patterns, applying panel data regressions. Findings show that global agricultural trade networks remain relevant, but are no longer sufficient in explaining certification. Fostering a favourable business environment - via providing secure land tenure and a functioning judicial system - as well as investing in transportation and information infrastructure may facilitate farmers' participation in certification schemes. Stringency of existing public regulations is helpful for overcoming entry barriers.
Keywords: O31; Q13; Q18; 330; global agricultural supply chains; GlobalG.A.P.; private food standards; organisational innovations; agricultural sector transformation